2018
DOI: 10.1002/mame.201800511
|View full text |Cite
|
Sign up to set email alerts
|

Self Assembly–Assisted Additive Manufacturing: Direct Ink Write 3D Printing of Epoxy–Amine Thermosets

Abstract: The use of self‐assembling, pre‐polymer materials in 3D printing is rare, due to difficulties of facilitating printing with low molecular weight species and preserving their reactivity and/or functions on the macroscale. Akin to 3D printing of small molecules, examples of extrusion‐based printing of pre‐polymer thermosets are uncommon, arising from their limited rheological tuneability and slow reactions kinetics. The direct ink write (DIW) 3D printing of a two‐part resin, Epon 828 and Jeffamine D230, using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 58 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…This rheological additive is known to create a 3D network through hydrogen bonding with epoxy polymer chains resulting in a gel-like structure. Epoxy resins containing the rheological additive exhibit shear thinning behavior through the disruption of the network structure, while the formation of hydrogen bonds imparts thixotropic properties, enabling time-dependent changes in viscosity [31]. Comparing flow behavior of samples NdFeB-a5EPX and NdFeB-a10EPX, it can be concluded that an increase in rheological additive content fostered strong shear thinning behavior, which is supported by a low flow index value.…”
Section: Viscosity and Flow Curve Analysismentioning
confidence: 92%
“…This rheological additive is known to create a 3D network through hydrogen bonding with epoxy polymer chains resulting in a gel-like structure. Epoxy resins containing the rheological additive exhibit shear thinning behavior through the disruption of the network structure, while the formation of hydrogen bonds imparts thixotropic properties, enabling time-dependent changes in viscosity [31]. Comparing flow behavior of samples NdFeB-a5EPX and NdFeB-a10EPX, it can be concluded that an increase in rheological additive content fostered strong shear thinning behavior, which is supported by a low flow index value.…”
Section: Viscosity and Flow Curve Analysismentioning
confidence: 92%
“…[297] The thixotropic behavior of the inks can be tailored through the interactions between their molecules or particles, which can be temporarily disrupted by a mechanical stimulus (i.e., shear force during the ink deposition process) and then reinstated upon deposition. [297,298]…”
Section: Materials Requirementsmentioning
confidence: 99%
“…The part maintains its shape during printing as a consequence of the rheological properties of the ink while the cross-linking takes place. 20 Ideally, DIW materials are able to maintain their shape provided that no external shear is applied; only during the extrusion process itself is the material able to flow. 11 The major advantage of DIW in polymers relies on the highly precise print features (below 100 μm) that are possible as a result of the use of automated print heads coupled with small diameter nozzles which control material flow, as well as the wide array of compatible materials that can be used, which include thermoplastic polymers and composites, thermosetting materials, hydrogels, graphene, ceramics, and even metals in specialized cases.…”
Section: ■ Overviewmentioning
confidence: 99%